1357. A Combination of Itraconazole and Amiodarone Is Highly Effective Against Trypanosoma cruzi Infection of Human Stem Cell-Derived Cardiomyocytes. (26th November 2018) - Sass, Gabriele; Madigan, Roy; Bozzi, Adriana; Sayed, Nazish; Wu, Joseph; Stevens, David
Abstract: Background: Trypanosoma cruzi is the etiologic agent of Chagas disease, which can result in severe cardiomyopathy. Trypanosoma cruzi is endemic to the Americas, and of particular importance in Latin America. In the United States and other nonendemic countries, rising case numbers have been observed. The only drugs available so far are benznidazole and nifurtimox, which have limited efficacy during chronic infection. We repurposed itraconazole, originally an antifungal, in combination with amiodarone, an antiarrhythmic, with the goal to interfere with Tc infection. Both drugs inhibit sterol synthesis, while amiodarone also inhibits calcium metabolism of Trypanosoma cruzi . Methods: Human pluripotent stem cells (HiPSC) were differentiated to cardiomyocytes (HiPSC-CM). Vero cells or HiPSC-CM were infected with the T. cruzi trypomastigotes Y strain in the presence of itraconazole and/or amiodarone. After 48 hours, infection and multiplication were evaluated by Giemsa stain. Benznidazole was used as a reference compound. Cell viability was verified by XTT assay. Results: Itraconazole and amiodarone showed dose-dependent interference with T. cruzi infection of Vero cells or HiPSC-CM. The combination of itraconazole and amiodarone was more potent than the single substances, or benznidazole at therapeutic concentrations, without affecting host cell metabolism. In addition to effects on infection, itraconazole, or amiodarone affected T. cruzi multiplication. Here, itraconazole/amiodarone combinations were more potent than either alone, both, in Vero cells, and HiPSC-CM. Conclusion: Our in vitro data suggest that a combination of itraconazole and amiodarone might serve as an effective new treatment option for Chagas disease, particularly cardiac involvement, in human and animal patients. Disclosures: All authors: No reported disclosures.